2003
DOI: 10.1159/000068874
|View full text |Cite
|
Sign up to set email alerts
|

Flupenthixol versus Risperidone: Subjective Quality of Life as an Important Factor for Compliance in Chronic Schizophrenic Patients

Abstract: Objective: The primary aim of this paper was to compare the effects of flupenthixol and risperidone on subjective quality of life and attitude towards medication in chronic schizophrenic patients with mainly negative symptoms. In a spectrum ranging from its typical end ‘haloperidol’ to its atypical end ‘clozapine’, flupenthixol has typical and atypical characteristics. Methods: The effects of flupenthixol versus risperidone were investigated in a multicenter, double-blind trial, whereas subjective quality of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 69 publications
3
13
0
1
Order By: Relevance
“…A single-blind naturalistic study in which patients were switched from FGAs to either risperidone, olanzapine or quetiapine showed significant improvement in several aspects of quality of life at 1-year follow-up (Voruganti et al 2002). No significant difference in subjective quality of life (EuroQuol-Visual Analogue Scale) could be detected in a double-blind trial comparing flupenthixol and risperidone, while the ability to cope with stress, to achieve something and to feel relaxed improved significantly more in the flupenthixol group (Hertling et al 2003).…”
Section: Efficacy Of First-generation and Second-generation Antipsychmentioning
confidence: 90%
“…A single-blind naturalistic study in which patients were switched from FGAs to either risperidone, olanzapine or quetiapine showed significant improvement in several aspects of quality of life at 1-year follow-up (Voruganti et al 2002). No significant difference in subjective quality of life (EuroQuol-Visual Analogue Scale) could be detected in a double-blind trial comparing flupenthixol and risperidone, while the ability to cope with stress, to achieve something and to feel relaxed improved significantly more in the flupenthixol group (Hertling et al 2003).…”
Section: Efficacy Of First-generation and Second-generation Antipsychmentioning
confidence: 90%
“…FGA first-generation antipsychotics, SGA second-generation antipsychotics were no significant differences between the groups concerning the improvement of negative symptoms and general psychopathology. Subjective quality of life, as an important factor for compliance in chronic schizophrenic patients, was investigated in a multi-centre, double-blind trial with 76 patients treated with flupentixol and 77 patients treated with risperidone (Hertling et al 2003). Both groups showed a significant improvement regarding subjective quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests that flupentixol has first-and second-generation characteristics and probable beneficial effects in patients with predominantly negative symptoms (Kühn et al 2000;Müller et al 2002;Philipp et al 2003;Hertling et al 2003;Gattaz et al 2004). We therefore compared the effectiveness and costs of patients treated with flupentixol with other first-and second-generation antipsychotics in a real world setting using routine data from four German sickness funds (Techniker Krankenkasse, AOK Baden-Wuerttemberg, AOK Westfalen-Lippe and AOK Berlin).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of quality of life, Hertling et al (2003) found that people with schizophrenia treated with flupentixol felt subjectively more relaxed and better able to deal with stress than those on risperidone.…”
Section: Flupentixol (Flupenthixol) (Table 1)mentioning
confidence: 99%